Recruitment of Low-wage Workers for a Time-sensitive Natural Experiment to Evaluate a Minimum Wage Policy: Challenges and Lessons Learned. Issue 3 (August 2021) - Shanafelt, Amy; Sadeghzadeh, Claire; Chapman, Leah; De Marco, Molly; Harnack, Lisa; Gust, Susan; Jackson, Melvin; Caspi, Caitlin
Natural experiments are often used for answering research questions in which randomization is implausible. Effective recruitment strategies are well documented for observational cohort studies and clinical trials, unlike recruitment methods for time-sensitive natural experiments. In this time-sensitive study of the impact of a minimum wage policy, we aimed to recruit 900 low-wage workers in Minneapolis, Minnesota, and Raleigh, North Carolina. We present our recruitment strategies, challenges, and successes for participant screening and enrollment of a difficult-to-reach population.